PENILAIAN RISIKO BENDUNGAN TILONG BERBASIS METODE INDEKS RISIKO - Hotma Lamtio Purba; Sukamta Sukamta; Kresno Wikan Sadono (Borneo Engineering : Jurnal Teknik Sipil, 2023)
Risk assessment aims to identify risks that may occur in various conditions, so that the necessary action plan can be carried out if the risk is unacceptable. In this study, the value of safety level in Tilong Dam, located at Kupang Regency, NTT is calculated.  The method used in this research is the risk index method. The method is based on a combination of importance of a dam factors, relative importance of physical conditions, and current condition from inspection. The result of this study shows that Tilong Dam has an importance of a dam factors (Idam) was 630, the total index risk was 116,55, and the safety level was 81,5. Tilong dam could be classified as satisfactory condition (safety level75), so that no action plan is needed because it is categorized as safe under normal and extraordinary load conditions.